Dietary fatty acids and the stress response of fish : - Anholt, R.D. van (Radboud Universiteit of Nijmegen, 1993)
A key factor in the production of fish in commercial aquaculture is the optimization of the artificial diets, not only to achieve optimal growth, but also to maximize fish health. Evidence is accumulating that dietary lipids, particularly the fatty acid composition, can have a direct effect on the fitness of the fish. This thesis aims to clarify the role played by the polyunsaturated fatty acid arachidonic acid (ArA, 20:4n-6) in fish, particularly in relation to the stress response and osmoregulation. A comparison was made between two species: Mozambique tilapia (Oreochromis mossambicus), a freshwater species that is able to fulfil its requirement for ArA by synthesising it from a precursor, and gilthead seabream (Sparus aurata), a seawater species that depends on the diet to supply this fatty acid.